Management of Sclerotinia rot of mustard through bioagents - V.S. GAUTAM and R.P. DANGI, R.B. GAUR*, R.N. SHARMA (Indian Phytopathology, 2010)
Systematic studies in laboratory, cage house and multilocation field trials were conducted (2002-03 to 2005-06) to find out the best mixed formulation of bioagent for controlling Sclerotinia rot {Sclerotinia sclerotiorum (ITCC ID No. 5784-04)} of Indian mustard (Brassica juncea). Out of twenty four bioagents tried five were selected for their biocontrol potential and effect on yield attributes (germination, vigour index) and grouped into different combinations for testing as seed dresser and foliar sprays. Multilocation field studies in lab and cage conditions revealed that Sclerotinia rot of mustard can be managed by seed treatment (@ 10 g/kg) and foliar spray (@ 0.2%) at 50 DAS with talc based mixed formulation (2 x 108 cfu/g) of Trichoderma hamatum (HP-20) + T. viride (Tv-1) in the ratio of 1 : 1 (w/w) followed by bioagent combination of T. harzianum (TG-1) + Gliocladium virens (Gv). Though both these combinations were statistically at par but mixed formulation of T. hamatum + T. viride were superior at most of the experimental fields. In vitro and cage house studies, some bioagents were effective but had no effect on germination and vigour index. Similarly bioagents when combined had higher potential in checking the disease than alone.